PERANAN DAN EFEKTIFITAS MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA LINGKUNGAN HIDUP DI BALI - Tri Darmayanti, Komang; Tjukup, I Ketut; Satyayudha Dananjaya, I Nyoman (Kertha Wicara : Journal Ilmu Hukum, 2012)
In Indonesia, the people may use an alternative dispute resolution to solve their cases.. Mediation is a popular alternative disputes resolution, because there are many advantages, such as use informal process, confidentially, low expense, and making decision between the parties. Environmental disputes is a one of many disputes that be able to use mediation. Because there are repressive effort and preventif effort on the agreement result. The parties who use mediation, also assisted by mediator as a neutral third person.
Keywords: Mediation, Mediator, Enviromental Disputes